CMOS differential and amplified dosimeter with field oxide N-channel MOSFETs - García Inza, Mariano Andrés (2014)
We propose the use of a CMOS differential circuit with inherent amplification to enhance the performance of n-channel field oxide MOSFETs as ionizing radiation dosimeters. These new dosimeters are aimed to be used in low dose applications such as X-ray diagnosis. The circuit is presented and described, and a discrete-level prototype was tested as regards sensitivity, temperature variations compensation and signal-to-noise ratio at different operation conditions. Results show that, comparing to a single MOSFET dosimeter, on chip amplification is possible along with temperature induced error attenuation. The highest sensitivity measured with respect to γ radiation was 0.4 V/rad. The circuit successfully measured the dose delivered in an X-ray image diagnosis environment with a sensitivity of approximately 0.5 V/rad.